The Influence of Trust and Communication on performance mediated by commitment - Rustinanah Rustinanah; Riski Eko Ardianto; Wachid Hasyim (Journal of Research in Social Science and Humanities, 2024)
This study discusses the effect of the Occupational Health and Safety (OHS) programme on employee productivity mediated by work-life balance on millennial generation employees in Bekasi Regency. This study uses a quantitative approach with a sample size of 96 samples. The sample calculation uses the Lemeshow formula. The results showed that the OHS programme affects employee productivity, work-life balance affects employee productivity, the OHS programme affects work-life balance, and the OHS programme affects employee productivity mediated by work-life balance.